Effects of calcitriol (1, 25-dihydroxy-vitamin D3) on the inflammatory response induced by H9N2 influenza virus infection in human lung A549 epithelial cells and in mice. Issue 1 (December 2017) - Gui, Boxiang; Chen, Qin; Hu, Chuanxia; Zhu, Caihui; He, Guimei
Abstract Background H9N2 influenza viruses circulate globally and are considered to have pandemic potential. The hyper-inflammatory response elicited by these viruses is thought to contribute to disease severity. Calcitriol plays an important role in modulating the immune response to viral infections. However, its unknown whether calcitriol can attenuate the inflammatory response elicited by H9N2 influenza virus infection. Methods Human lung A549 epithelial cells were treated with calcitriol (100 nM) and then infected with an H9N2 influenza virus, or infected and then treated with calcitriol (30 nM). Culture supernatants were collected every 24 h post infection and the viral growth kinetics and inflammatory response were evaluated. Calcitriol (5 mg/kg) was administered daily by intraperitoneal injection to BABL/c mice for 15 days following H9N2 influenza virus infection. Mice were monitored for clinical signs of disease, lung pathology and inflammatory responses. Results Calcitriol treatment prior to and post infection with H9N2 influenza significantly decreased expression of the influenza M gene, IL-6, and IFN-β in A549 cells, but did not affect virus replication. In vivo, we found that calcitriol treatment significantly downregulated pulmonary inflammation in mice 2 days post-infection, but increased the inflammatory response 4 to 6 days post-infection. In contrast, the antiviral cytokine IFN-β was significantly higher in calcitriol-treated mice than in the untreated infected mice at 2 days post-infection, but lower than in untreated infected mice on days 4 and 8 post-infection. The elevated levels of pro-inflammatory cytokines and the decreased levels of antiviral cytokine are consistent with the period of maximum body weight loss and the lung damage in calcitriol-treated mice. Conclusions These results suggest that calcitriol treatment might have a negative impact on the innate immune response elicited by H9N2 infection in mice, especially at the later stage of influenza virus infection. This study will provide some novel insights into the use of calcitriol to modulate the inflammatory response elicited by influenza virus infection in humans.